2019
DOI: 10.1002/qj.3448
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of ground‐based GNSS Zenith Total Delay temporal observation error correlations using data from the NOAA and E‐GVAP networks

Abstract: In preparation for possible higher frequency assimilation of ground-based Global Navigation Satellite System (GB-GNSS) Zenith Total Delay (ZTD) observations at Environment and Climate Change Canada (ECCC), two popular diagnostic methods are applied to observation-minus-background and observation-minus-analysis departures from the ECCC Global Deterministic Prediction System (GDPS) to estimate temporal ZTD observation error correlations within the 6 h assimilation window. The GDPS uses a four-dimensional ensembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The source codes developed as part of this study have been delivered to FNMOC and the operational NAVGEM data assimilation system is scheduled to begin in August 2022. Additional focus on optimizing the data usage, such as spatial thinning (Poli et al., 2007) and better uncertainty estimation (S. Macpherson & Laroche, 2019), is additional future directions to pursue. The static bias calculation scheme in the current study can also be further modified in a real‐time operational cycled system, where the biases can be estimated with a moving average of observation‐minus‐background differences using a time period prior to the analysis time.…”
Section: Discussionmentioning
confidence: 99%
“…The source codes developed as part of this study have been delivered to FNMOC and the operational NAVGEM data assimilation system is scheduled to begin in August 2022. Additional focus on optimizing the data usage, such as spatial thinning (Poli et al., 2007) and better uncertainty estimation (S. Macpherson & Laroche, 2019), is additional future directions to pursue. The static bias calculation scheme in the current study can also be further modified in a real‐time operational cycled system, where the biases can be estimated with a moving average of observation‐minus‐background differences using a time period prior to the analysis time.…”
Section: Discussionmentioning
confidence: 99%
“…In this method, assuming that the observation errors are spatially uncorrelated (or have a small length-scale in comparison to the spatial correlations of the background errors) allows one to distinguish and estimate the statistics of the observation and background errors. The HL method has been successfully extended to estimate multichannel observation-error covariances (Garand et al, 2007;, temporal correlations of observation errors (Macpherson and Laroche, 2019), and to incorporate spatial observation-error correlations (Eresmaa and Järvinen, 2005). In the context of atmospheric chemistry, chemical error statistics have been obtained by using the HL method with a single polar-orbiting satellite by using the distance between consecutive measurements along the satellite track (Ménard et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As the D05 method is often easier to apply for high-dimensional problems, this method gained popularity in numerical weather prediction, especially for the estimation of satellite observation-error covariances Stewart et al, 2014;Weston et al, 2014;Todling, 2015;Gauthier et al, 2018). The D05 method has also been used to estimate model-error variances in ensemble Kalman filtering (Li et al, 2009), Doppler radar radial wind error correlations (Waller et al, 2016b), spatial and temporal observation-error correlations for ground-based Global Navigation Satellite System (GNSS) Zenith Total Delay observations (Bennitt et al, 2017;Macpherson and Laroche, 2019), and observation errors in multi-species atmospheric chemical constituent assimilations (Skachko et al, 2016). Although devised as an iterative algorithm, most operational applications of the D05 algorithm only apply one iteration due to the added computational cost of computing multiple analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boniface et al [24] identified that the impact of ZTD assimilation in AROME model depends on the rainfall synoptic conditions, while Arriola et al [16] highlighted the importance of ZTD observations processing before the assimilation application. More recent studies focused on investigating different observational bias correction methods and on estimating spatiotemporal correlations of observations errors for application on ZTD data used for data assimilation [25][26][27].The literature review shows that improvements in the precipitation forecast skill may be gained by assimilating ZTD observations into NWP models. However, regional studies using the WRF modeling system are relatively rare (e.g., Rohm et al [28]), while no research focusing on Greece has ever been conducted.…”
mentioning
confidence: 99%